DOSAGEM DE ANTITOXINA DIFTÉRICA CIRCULANTE PELA REAÇÃO DE HEMAGLUTINAÇÃO PASSIVA E SUA RELAÇÃO COM A PROVA DE SCHICK EM ESTUDANTES DE MEDICINA - Guedes, José da Silva; Iaria, Sebastião Timo; Cotillo Z., Luiz G.; Santos, José Antonio Alves dos; Bourroul, Geraldo Paulo (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1966)
The results of the Schick tests and the levels of diphtheria antitoxin as determined by passive hemagglutination test were compared. For this investigation, the 2nd year students of the Faculdade de Ciências Médicas dos Hospital da Santa Casa de Misericórdia de São Paulo (Brazil) were chosen, as they would soon be subject to contact in communicable disease wards. It was not possible to obtain precise information regarding their diphtheria immunization history. The Schick test was performed in 118 students, 19-30 years old of both sexes showing 35 (29,7%) Schick-positives,76 (64.4%); Schick-negatives and 7 (5.9%) pseudo-reactors. No combined reaction was observed. The circulating diphtheria antitoxin leveis were detcrmincd in the sera from 110 of the 118 students. These 110 students comprised 35 Schick-positives, 69 Schick-negatives and 6 pseudo-positive reactions. From of the 35 Schick-positives, 27 (77,1%) had antitoxic leveis below 0.01 U./ml and (22,9%) had titers of O.01 U./ml ore more. Of tthe 69 Schick-negatives 51 (73,9%) showed antitoxic leveis of O.01 U./ml or more and 18 (26.1%) had titers below O.O1 U/ml. Of the 6 subjects with pseudo-positive reactions, 5(83.4%) showed antitoxic titers of O.01 U. /ml or more and one had than 0.01 U./ml. The passive hemagglutination test revealed itself as an acceptable method. Tt might bc useful in revealing diphtheria susceptihility in mass studics, as it is simply and rapidly performed.